2008
DOI: 10.1016/j.jprot.2007.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Snake venomics of the South and Central American Bushmasters. Comparison of the toxin composition of Lachesis muta gathered from proteomic versus transcriptomic analysis

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. were identified in L. muta and L. stenophrys venoms. In addition, both venoms contained a large number of brady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 55 publications
1
85
0
13
Order By: Relevance
“…Firstly, these messengers may exhibit transient, individual or a temporal expression patterns over the life time of the snake. Alternatively, mRNAs whose predicted polypeptides were not found to be secreted in venom may represent very low abundance toxins that play a hitherto unrecognised physiological function in the venom gland, or may simply represent a hidden repertoire of non-translated orphan molecules which may eventually become functional for the adaptation of snakes to Table 1 Overview of the relative occurrence of proteins (in percentage of the total HPLC-separated proteins) of the toxin families in the venoms of Sistrurus catenatus catenatus (SCC), Sistrurus catenatus tergeminus (SCT), and Sistrurus catenatus edwardsii (SCE) from USA [34]; Sistrurus miliarius barbouri (SMB) from USA [52]; the Tunisian snakes Cerastes cerastes cerastes (CCC), Cerastes vipera (CV) and Macrovipera lebetina transmediterranea (MLT) [48]; African Bitis arietans (BA) [50]; Bitis gabonica gabonica (BGG) [49]; Bitis gabonica rhinoceros (BGR), Bitis nasicornis (BN), and Bitis caudalis (BC) [56]; Echis ocellatus (EO) [51]; Lachesis muta (LM) [53]; Crotalus atrox (CA), and Agkistrodon contortrix contortrix (ACC) from USA (Calvete et al, unpublished); Armenian vipers Macrovipera lebetina obtusa (Mlo), and Vipera raddei (Vr) [54]; Atropoides picadoi (Api), and Atropoides mexicanus (Amex) [57] from Costa Rica; Bothrops asper (Bas) from the Caribbean (C) and the Pacific versants of Costa Rica [60]; Lesser Antillean pitvipers Bothrops caribbaeus (Bcar) (Santa Lucía), and Bothrops lanceolatus (Blan) (Martinique) [58]; Brazilian Bothrops fonsecai (Bfon), and Bothrops cotiara (Bco) [59]; Bothriechis lateralis (Bolat), and Bothriechis schlegelii (Bosch) [55] from Costa Rica; and Lachesis stenophrys (Lste) [53] changing ecological niches and prey habits. These data suggest that the final composition of venom is influenced by transcriptional and post-translational mechanisms that may be more complex than previously appreciated.…”
Section: Snake Venomics: Proteomic Tools For Studying the Protein Commentioning
confidence: 99%
“…Firstly, these messengers may exhibit transient, individual or a temporal expression patterns over the life time of the snake. Alternatively, mRNAs whose predicted polypeptides were not found to be secreted in venom may represent very low abundance toxins that play a hitherto unrecognised physiological function in the venom gland, or may simply represent a hidden repertoire of non-translated orphan molecules which may eventually become functional for the adaptation of snakes to Table 1 Overview of the relative occurrence of proteins (in percentage of the total HPLC-separated proteins) of the toxin families in the venoms of Sistrurus catenatus catenatus (SCC), Sistrurus catenatus tergeminus (SCT), and Sistrurus catenatus edwardsii (SCE) from USA [34]; Sistrurus miliarius barbouri (SMB) from USA [52]; the Tunisian snakes Cerastes cerastes cerastes (CCC), Cerastes vipera (CV) and Macrovipera lebetina transmediterranea (MLT) [48]; African Bitis arietans (BA) [50]; Bitis gabonica gabonica (BGG) [49]; Bitis gabonica rhinoceros (BGR), Bitis nasicornis (BN), and Bitis caudalis (BC) [56]; Echis ocellatus (EO) [51]; Lachesis muta (LM) [53]; Crotalus atrox (CA), and Agkistrodon contortrix contortrix (ACC) from USA (Calvete et al, unpublished); Armenian vipers Macrovipera lebetina obtusa (Mlo), and Vipera raddei (Vr) [54]; Atropoides picadoi (Api), and Atropoides mexicanus (Amex) [57] from Costa Rica; Bothrops asper (Bas) from the Caribbean (C) and the Pacific versants of Costa Rica [60]; Lesser Antillean pitvipers Bothrops caribbaeus (Bcar) (Santa Lucía), and Bothrops lanceolatus (Blan) (Martinique) [58]; Brazilian Bothrops fonsecai (Bfon), and Bothrops cotiara (Bco) [59]; Bothriechis lateralis (Bolat), and Bothriechis schlegelii (Bosch) [55] from Costa Rica; and Lachesis stenophrys (Lste) [53] changing ecological niches and prey habits. These data suggest that the final composition of venom is influenced by transcriptional and post-translational mechanisms that may be more complex than previously appreciated.…”
Section: Snake Venomics: Proteomic Tools For Studying the Protein Commentioning
confidence: 99%
“…And as previously mentioned, some differences among Lachesis species had been observed (23). Furthermore, geographical variations in the venom components demand the development of regional immunodiagnostic tests specific to snakes that inhabit a given region (25).…”
Section: Discussionmentioning
confidence: 95%
“…A recent study to develop a proteomic characterization of venoms of L. muta from Brazil and L. stenophrys from Costa Rica revealed that these venoms share (or contain highly similar) proteins, in particular bradykinin-potentiating/ C-natriuretic peptide (BPPs), serine proteinases, a galactose-specific C-type lectin, and L-amino acid oxidase (LAO). However, they dramatically differ in their respective PLA 2 complement (23).…”
Section: Discussionmentioning
confidence: 98%
“…Algumas atividades farmacológicas já foram descritas como formação de edemas, citotoxicidade, agregação plaquetária, ação hipotensiva, apoptose de células endoteliais, o que pode contribuir para o sangramento prolongado na parede dos vasos danificados pela mordida, entre outras (Ahn et al, 1997;Ali et al, 2000;Braga et al, 2008;Li et al, 1994;Suhr and Kim, 1996). Apesar de bem descritas nas peçonhas de diversas serpentes, ainda existem poucos estudos descrevendo as Laminoácido oxidases presentes em peçonhas laquéticas (Kuch et al, 1996;Sanz et al, 2008).…”
Section: +unclassified
“…Entretanto, não é incomum encontrar serpentes com até 3,0 metros de comprimento (Sanz et al, 2008). Essa família ainda engloba dois outros gêneros de considerável importância, Crotalus e Bothrops (Damico et al, 2005a).…”
unclassified